COPING WITH LOSS: THE ROLE OF GUIDANCE AND COUNSELING IN SUPPORTING GRIEVING COUNSELEE - Mutia Khaira; Nur Widyanti; Nadia Aulia Nadhirah (Study Program Guidance and Counseling, Univesitas Pendidik, 2024)
Death in a family can impact every family member. The impact of the death of a loved one can be physical, spiritual and social. On the other hand, grief can also have an impact on a person's mental condition, such as sleep disorders, eating disorders, difficulty concentrating, and excessive anxiety. Socially, people who swear can then withdraw from their social environment, feel inferior, and even isolate themselves. Grief is a complex emotional response to the loss of a loved person or object. This emotional response is something normal and important for humans, as part of their life development. It is hoped that this research can help individuals who are in this phase with several ways of guidance and counseling that can support individuals who are experiencing loss and sadness. This research is a type of qualitative research using the literature study research method by reviewing various literature studies required in this research.